Determinants of Inadequate Minimum Dietary Diversity Intake Among Children Aged 6–23 Months in Sub-Saharan Africa: Pooled Prevalence and Multilevel Analysis of Demographic and Health Survey in 33 Sub-Saharan African Countries - Belay, Daniel Gashaneh; Aragaw, Fantu Mamo; Teklu, Rediet Eristu; Fetene, Samrawit Mihret; Negash, Wubshet Debebe; Asmamaw, Desale Bihonegn; Fentie, Elsa Awoke; Alemu, Tewodros Getaneh; Eshetu, Habitu Birhan; Shewarega, Ever Siyoum (Frontiers in Nutrition, 2022)
Background: Undernutrition is linked to just under half of all deaths of children aged under five in annually and varied across socio-economic classes. Moreover, inappropriate feeding practices during the first 1000 days result in significant threats to child health by impaired cognitive development, compromised educational achievement and low economic productivity . Therefore, this study aimed to assess the pooled magnitude and determinants of inadequate MDD intake among children aged 6-23 months in SSA . Methods: A total of 77,887 weighted samples from Demographic and Health Survey datasets of SSA countries were used for this study. A multilevel binary logistic regression model was fitted. P-value < 0.05 with 95%CI was taken to declare statistical significance. Results: The pooled magnitude of inadequate MDD intake among children age 6-23 months in SSA was 76.53 % (95%CI: 73.37%, 79.70%), ranges from 50.5% in South Africa to 94.40% in Burkina Faso. Individual level factors such as; having secondary &above women education [AOR=0.66; 95%CI; 0.62, 0.70], having employed women [AOR=0.76; 95%CI; 0.72, 0.79], having household media exposure [AOR= 0.69; 95%CI; 0.66, 0.72], richest wealth [AOR= 0.46; 95%CI; 0.43, 0.50], having health institution delivery [AOR= 0.87 ;95%CI; 0.83, 0.91] whereas, community level factor such as rural residence [AOR= 1.29; 95%CI; 1.23, 1.36], live in upper middle income country [AOR= 0.42; 95%CI; 0.38, 0.46] have significant association with inadequate MDD intake among children aged 6-23 months. Inadequate MDD intake among children aged 6-23 months in SSA was disproportionately concentrated on the poor households (pro-poor) [C= -0.24; 95% CI: -0.22, -0.0.26]. Conclusion and recommendations: Inadequate minimum dietary diversity intake among children aged 6-23 months in SSA is relatively high. Variables such as; secondary &above maternal education, having an employed mother, having exposure to media, richest wealth, having health institution delivery, and living in the upper middle-income country have a significant negative association, whereas living in rural residence has a significant positive association with inadequate MDD intake. These findings highlight, to increase the MDD intake in the region policymakers and other stakeholders had better give prior attention to enhancing household wealth status, empowering women, and media exposure.